Formulation and Evaluation of Chronotherapeutic Delivery of Sacubitril Valsartan for Management of Hypertension - Aleti, Rajeswari; Nijhawan, Monika; Sailaja, Gunnam (Indian Journal of Pharmaceutical Education and Research, 2025)
Introduction: Early morning surge in blood pressure is a major cause of sudden cardiac arrest. Objectives: Development and evaluation of chronomodulated Compression Coated Tablets (CCT) for bedtime dosing of sacubitril-valsartan for the management of cardiac arrest. Materials and Methods: The tablets contain fast disintegrating inner core of sacubitril-valsartan coated by compression coating technique with a hydrophilic polymer. Various ratios of HPMC K100M were used as coating polymer and investigated to achieve the expected lag time of five hr. The micromeritic and tableting properties of core and CCT were evaluated. Further, the drug excipient compatibility in optimized formulations was investigated. Accelerated and long-term stability studies were performed to optimize compression coated tablets. Results: The tableting characteristics of core and compression coated tablets were found to be within limits specified in Indian Pharmacopeia. The Core tablets (CP4) prepared using 6% crospovidone showed good similarities with marketed IR (Immediate release) tablets (f2-82.65). The drug release profile of compression coated tablets (H4) exhibited preprogrammed lag time of 5 hr followed by burst release of drug (98%) from core tablet. The controlled onset of drug release was due to formation of viscous gel layer by HPMC K100M at the initial stages and balanced mechanism of solvent penetration and coat erosion. Absence of significant interactions in FTIR studies reveals drug and polymer compatibility. Compression coated tablets were found to be stable after accelerated and long-term stability studies. Conclusion: The optimized formulation H4 formulated using 2:3 ratio of HPMC/lactose in the coating exhibited a preprogramed lag phase before the burst release of the drug from the core and achieved chronotherapeutic delivery of sacubitril-valsartan to minimize the incidence of early morning surge and cardiac arrest in hypertensive patients.
Keywords: Sacubitril-valsartan; HPMCK100M; lactose; Compression coating; Chronotherapeutic drug delivery; Bedtime dosing